The History and the Future of the Psychology of Filial Piety: Chinese Norms to Contextualized Personality Construct - Bedford, Olwen; Yeh, Kuang-Hui (Frontiers in Psychology, 2019)
In the field of psychology, filial piety is usually defined in terms of traditional Chinese culture-specific family traditions. The problem with this approach is that it tends to emphasize identification of behavioral rules or norms, which limits its potential for application in other cultural contexts. Due to the global trend of population aging, governments are searching for solutions to the accompanying financial burden so greater attention is being focused on the issue of elder care and its relevance to filial practices. We contend that the psychological investigation of filial piety in Chinese societies has progressed to the point that it can now provide a solid structure for research targeting intergenerational relations in other cultures. We describe an indigenous psychology approach that integrated Chinese historical, philosophical, and social trends to construct a model of filial piety in terms of the dual reciprocal and authoritarian filial aspects underlying parent-child relations: the dual filial piety model (DFPM). We use this model to re-conceptualize filial piety from its usual definition as a set of Chinese culture-specific norms to a contextualized personality construct represented by a pair of culturally-sensitive psychological schemas of parent-child interaction. We then describe how the DFPM can provide a framework for research on filial relations on individual, structural, societal, and cross-cultural levels. We conclude with a discussion of how the model may be able to integrate and extend Western research on intergenerational relations and contribute to the issue of elder care beyond Chinese societies.